Factor analysis in itaconic acid fermentation using filtered POME by aspergillus terreus IMI 282743 - Jamaliah Md. Jahim,; Noor Intan Shafinas Muhammad,; Wu, Ta Yeong (2006)
The production of itaconic acid by Aspergillus terreus IMI 282743 from filtered Palm Oil Mill Effluent (POME) as an added supplement was investigated. The factor analysis method was applied to screen the most influential parameters for the production of itaconic acid. Through this analysis, the filtered POME was proven to be a significant parameter in the fermentation. In addition, the parameter could be considered as an inducer to the production of itaconic acid since the addition of filtered POME into the media was able to increase the itaconic acid concentration. The production of itaconic acid was achieved up to 5.76 g/L in shake flask fermentation from production medium consisted of 56 mL of filtered POME containing 51% of filtered POME. It is also believed that if POME formulated media is used with the industrial strain, higher concentration of itaconic acid could be attained since according to some researches, it has been shown that industrial type strain is capable to produce more of the acid. Other parameters that were found to have significant influence on the itaconic acid production include percentage of glycerol, pH , temperature, concentration of NH4NO3 and agitation speed